A Sonographer's Step-by-Step Approach for Preventing Transmission of COVID-19. (January 2021) - Wessner, Corinne E.; Nelson, JoAnn; Mott, Sarah; Francesco, Maria; Needleman, Laurence
The 2019 novel coronavirus, known as COVID-19, has greatly affected the way sonographers care for their patients. Sonography can be a useful imaging tool for surveillance and diagnosis of various conditions associated with COVID-19 patients or patients under investigation (PUIs). Currently, there are limited resources and protocols for preventing the transmission of COVID-19 from ultrasound equipment. Our institution has created a detailed protocol for scanning COVID-19 patients or PUIs to address this important issue.